Thyroxin Levels Associated with Current Suicide Attempts: A Case Control and Follow-Up Study. Issue 3 (1st September 2016) - Ozcan, Halil; Yucel, Atakan; Atis, Omer; Yucel, Nermin; Bilen, Arzu; Emet, Mucahit; Gur, Sultan Tuna Akgol
ABSTRACT: Objective : Suicide is a complex behavior concerning a number of psychological, biological, social and cultural factors. It is also an important public issue, as well as one of the leading causes of death. We aimed to examine the relationship between suicide attempt and thyroid hormones in suicide attempters and healthy controls and aimed to clarify whether any of the thyroid hormone levels may have predicted current or future suicide attempts. Method : This study comprised 358 participants (115 suicide attempters, 243 controls). Thyroid hormone levels including free T3, free T4, and TSH of all participants were explored. For predicting future suicide attempts using our hospital database and the database of the Republic of Turkey Social Security Institution, via International Classification of Diseases (ICD) diagnostic codes related to suicide data of future suicide attempts of the study participants were collected. Participants were people without previous history of any thyroid disorder or chronic disease (endocrinological, pulmonary, gastrointestinal, neurological, infectious and neoplastic diseases, hepatic, renal or cardiac failure) that may affect thyroid hormone levels. The participants who were on any thyroid hormone or drug that may affect thyroid hormone levels (e.g., lithium, carbamazepine, oral contraceptives etc.) alcoholism or drug abuse other than nicotine, pregnancy, detected possible thyroid disease during procedure, intellectual disability, rejection of blood tests, missing data on topics mentioned above, were all excluded. Results : Thyroid hormone levels of both groups were within normal range. Groups differed with regard to FT4 (thyroxin), TSH and FT3/FT4 levels. A logistic regression model indicated that suicide attempters were 32.7 times more likely to have higher FT4 levels (OR: 32.7; 95% CI: 5.3-202.9; p<0.0001), 1.7 times more likely to have higher TSH levels (OR: 1.7; 95% CI: 1.2-2.3; p=0.002), 2.5 times more likely to have lower FT3/FT4 levels (OR: 0.4; 95% CI: 0.2-0.8; p=0.008) than controls. Diagnostic validity of FT4 was found to be good in differentiating patients with both groups (ROC area under the curve=0.821; 95% CI: 0.77-0.87; p<0.0001). The cut-off point for FT4 of 1.15 ng/dl gave a high sensitivity (85%) and specificity (70%). Conclusion : Thyroid function test measurement may be used as discriminative cut-offs between suicide attempters and healthy subjects. None of the thyroid hormones indicated future suicide attempts. Higher FT4, TSH, and lower FT3/FT4 levels are independently associated with suicide attempt. FT4 may be a useful marker to predict current suicide attempt.